2022
DOI: 10.3390/microorganisms10051043
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Starvation–Survival Response of Edwardsiella piscicida and E. tarda in Freshwater Microcosms, at Various Temperatures

Abstract: Edwardsiella piscicida is an important fish pathogen responsible for economic losses in global aquaculture, and E. tarda is also a human zoonotic pathogen. In this study, the survival of E. piscicida and E. tarda strains kept in filtered and sterilized lake water microcosms was investigated during a 20-week period at 7 °C, 15 °C and 25 °C, as well as its pathogenicity retention during a starvation period. E. tarda V43.2 stayed culturable for 6 weeks at 7 °C, 9 weeks at 25 °C and 12 weeks at 15 °C. Both E. pisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Although the pathogenicity of Legionella pneumophila reduced after entering VBNC state by heat treatment, the VBNC cells could still infect amoebae (Cervero‐Arago et al., 2019). Under starvation at 7°C, Esteve and Alcaide (2022) found that Edwardsiella piscicida V12.1, E. piscicida V57.2, and E. tarda V43.2 could enter the VBNC state at 14, 15, and 7 weeks, respectively. Among them, VBNC cells of E. piscicida V12.1 and E. piscicida V57.2 could still resuscitate after entering the VBNC state for 2 weeks, and the number of the resuscitated cells reached 0.7×10 6 CFU/g of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenicity of Legionella pneumophila reduced after entering VBNC state by heat treatment, the VBNC cells could still infect amoebae (Cervero‐Arago et al., 2019). Under starvation at 7°C, Esteve and Alcaide (2022) found that Edwardsiella piscicida V12.1, E. piscicida V57.2, and E. tarda V43.2 could enter the VBNC state at 14, 15, and 7 weeks, respectively. Among them, VBNC cells of E. piscicida V12.1 and E. piscicida V57.2 could still resuscitate after entering the VBNC state for 2 weeks, and the number of the resuscitated cells reached 0.7×10 6 CFU/g of fish.…”
Section: Discussionmentioning
confidence: 99%
“…It includes five species: Edwardsiella hoshinae , Edwardsiella tarda , Edwardsiella ichtaluri , Edwardsiella piscicida , and Edwardsiella anguillarum (Miniero Davies et al 2018; da Costa et al 2022; Ziarati et al 2022). These bacteria are commonly known as disease agents in aquaculture and are associated with the systemic disease edwardsiellosis (Esteve and Alcaide 2022). Edwardsiella tarda , an opportunistic and zoonotic pathogen, has a broad host range, infecting birds, mammals, reptiles, fish, and humans (White et al 1973; Reichley et al 2017; Buján et al 2018).…”
mentioning
confidence: 99%